A new and rigorous SPN theory – Part III: A succinct summary of the GSPN theory, the P3 equivalent GSP3(3) and implementation issues. (September 2018) - Chao, Yung-An
Abstract: For the interest of readers who do not need to deal with detailed mathematics, a succinct summary of the newly developed GSPN theory (Chao, 2017 ) is given in this technical note. A streamlined presentation of the idea, concept, logic, formulation and the physics of the theory is given here such that the readers can more easily comprehend the overall picture and the explicit resulting equations to be used in implementation. The mathematical details are referred to the previous papers (Chao, 2016, 2017). All the relevant equations for the P3 equivalent GSP 3 ( 3 ) theory are explicitly given. Issues of numerical implementation of the theory are discussed, and potentially viable methods are suggested and conceptually described.